2022
DOI: 10.1038/s41420-022-00979-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of m6A methylation of circDLC1 mediated by RNA methyltransferase METTL3 in the malignant proliferation of glioma cells

Abstract: Glioma is an intracranial malignant tumor and remains largely incurable. Circular RNAs are prominent modulators in glioma progression. This study investigated the function of circular RNA DLC1 (circDLC1) in the malignant proliferation of glioma cells. circDLC1 expression in glioma tissues and cells was determined using RT-qPCR. The effect of circDLC1 on the malignant proliferation of glioma cells was analyzed using CCK-8, colony formation, and EdU staining assays. METTL3, miR-671-5p, and CTNNBIP1 expressions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Other circRNAs may also prevent the proliferation of glioma cells and have a protective value. An example is circDCL1, whereby upregulation of this circRNA through METTL3-mediated m6A modification repressed the malignant proliferation of glioma cells ( 133 ). Recent studies also suggest that cicRNAs can affect multiple pathways of gliomagenesis, including the tumor microenvironment.…”
Section: Discussion With Biomarkersmentioning
confidence: 99%
“…Other circRNAs may also prevent the proliferation of glioma cells and have a protective value. An example is circDCL1, whereby upregulation of this circRNA through METTL3-mediated m6A modification repressed the malignant proliferation of glioma cells ( 133 ). Recent studies also suggest that cicRNAs can affect multiple pathways of gliomagenesis, including the tumor microenvironment.…”
Section: Discussion With Biomarkersmentioning
confidence: 99%
“…Accumulating evidence has revealed the unique role of m6A RNA methylation in the genesis and development of cancer including glioma. A series of studies using the knockdown model of METTL3 and METTL14 observed a reduction of m6A extent accompanied by upregulation of oncogenes and downregulation of tumor suppressors [20,21] . On the contrary, overexpression of METTL3 leads to decreased proliferation and migration of glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research into the molecular mechanism of glioma malignant proliferation has sparked widespread concern. By using m 6 A level detection and MeRIP assays, Wu et al discovered that METTL3-mediated m 6 A modification can enhance the stability and expression of circDLC1, thereby promoting the competitive binding of circDLC1 and miR-671-5p, facilitating Catenin Beta Interacting Protein 1 (CTNNBIP1) transcription, and ultimately suppressing the malignant proliferation of glioma cells (Wu et al 2022).…”
Section: Gliomamentioning
confidence: 99%